Extracellular potassium concentration and focal electrical potentials elicited in the cerebral cortex of rat by interhemispheric stimulation - Machek, J; Ujec, E; Pavlík, V (Neuroscience letters, 1976)
All points in the time course of the evoked and self-sustained, DC-recorded potentials elicited by repetitive interhemispheric stimulation were found to remain negative by -1 mV and more with respect to the prestimulation DC level only when the coinciding, directly recorded, extracellular potassium concentration was 11 mM. A slow oscilloscope sweep displayed the -1 mV level as a virtual line limiting the initial positive waves of the interhemispheric response. This line, approximately parallel with the potassium concentration record of around 11 mM, probably expresses the potassium-dependent membrane depolarizations, which were not revealed at lower potassium concentrations. The evoked and self-sustained potentials coinciding with the latter were displayed in negative as well as positive values.